2016
DOI: 10.1111/anu.12381
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phosphorylated protein concentrate of pumpkin seed meal on growth and digestive enzymes activity of silver catfish (Rhamdia quelen)

Abstract: The present study aimed to determine the growth and activity of proteolytic digestive enzymes of silver catfish (Rhamdia quelen) fed by replacing increased fish meal in the diet by either phosphorylated protein concentrate or pumpkin seed meal (PPCPS). Five experimental diets were formulated with levels: 0 (control), 25 (25% pumpkin seed meal (PSM) and 25% PPCPS) and 50% (50% PSM and 50% PPCPS). Crude protein from fish meal was replaced either by PSM or PPCPS crude protein. Each diet was fed to four replicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 45 publications
0
13
0
2
Order By: Relevance
“…The provision of diets containing up to 20% of HSM improved the growth of silver catfish without impairing food efficiency. Silver catfish is able to take advantage of different plant protein sources in the diet (Dalcin et al, ; Gourlat et al, ; Lovatto et al, ). High inclusion levels of plant protein sources in the diets leads to deficiency of essential amino acids and may compromise growth (Gatlin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The provision of diets containing up to 20% of HSM improved the growth of silver catfish without impairing food efficiency. Silver catfish is able to take advantage of different plant protein sources in the diet (Dalcin et al, ; Gourlat et al, ; Lovatto et al, ). High inclusion levels of plant protein sources in the diets leads to deficiency of essential amino acids and may compromise growth (Gatlin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…in the catfish intestine optimum pH ranged between 8.5 to 10 Also, the catfish stomach showed optimum proteolytic activity at pH 3.0 and 4.0 however, Abdel-Warith et al (2013) reported that the data obtained of tilapia showed optimum proteolytic activity in tilapia intestine was at pH 7.0-8.5, whereas, in the stomach was at pH 1.5-3.0, this gives an indicator that in thick-walled muscular stomachs, such as C. gariepinus, the pH is quite high at around 4. Lovatto et al (2017) argued that higher trypsin activity in silver catfish (Rhamdia quelen) fed diets containing pumpkin seed meal represents the body's attempt to increase the digestibility of protein, that adverse in increased activities of the proteolytic. Alarcon et al (2001) who found that the connection between the trypsin activities in the intestinal and the digestibility of protein in L. argentiventris and L. novemfasciatus, inhibitor activity of the enzyme appears to be offset by raising the secretion of enzymes proteolytic and increased protein absorption in distal parts of the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…These digestive enzymes, like others, are active into the proximal intestine. The hydrolysis of protein intake from the diets which occurs by these enzymes that active in the proximal intestine, serve to break down the protein to simple molecules that can then be absorbed throughout the intestine and used in the metabolic process (Lovatto et al, 2017). While some studies have focused their attention on the influence of different substitute plant proteins on fish growth and feed utilization, few have looked at how diet changes the activities of digestive enzymes) Xu et al (2012) and Zhao et al (2016).…”
Section: Introductionmentioning
confidence: 99%
“…In general, the use of plant protein concentrates in fish diets results in a reduced activity of trypsin (Krogdahl, Bakke‐Mckellep, & Baeverfjord, ), which is caused by the presence of antinutritional factors (Pavasovic, Anderson, Mather, & Richardson, ). However, the occurrence of increased enzyme activity is explained by the body's attempt to enhance the digestibility of the ingested protein, reflecting a higher proteolytic activity (Lovatto et al, ). However, the results found in this study showed that the trypsin and chymotrypsin enzyme activities were not affected by the dietary inclusion of RBPC.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical and enzymatic methods can also be used to improve protein digestibility, reduce fibre content and increase the amino acid content of plant protein sources (Lovatto et al, ). By reducing the fibre content, the amino acid level and crude protein level also increased in the raw material (Palmegiano et al, ).…”
Section: Introductionmentioning
confidence: 99%